GENERATING GIS DATABASE OF STREET TREES USING MOBILE LIDAR DATA - M. Yadav; P. Khan; A. K. Singh; A. K. Singh; B. Lohani (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
Mobile LiDAR captures complete details of street trees located along roadway and it is most efficient tool for executing large scale projects for road side trees mapping. Information of road-side trees locations and their morphological characteristics are essential for road widening project planning, road safety and autonomous vehicles. We propose a method to generate GIS database of street trees using information of automatically extracted street trees using mobile LiDAR data. Proposed method first organizes mobile LiDAR input data in partially overlapping cylinders and then morphological characteristics of tree crown and trunk, respectively are used to detect trees falling within cylinders. Finally complete tree structure point cloud is recovered from cylinder by vertical cylinders fitting to crown and trunk separately. The proposed method is tested on point cloud data acquired by StreetMapper 360 of 57 m long roadway. Completeness and correctness of 88.24% and 93.75% respectively are obtained in test site.